The determinant of dividend policy among plantation company in Malaysia / Hamiza Hamzah - Hamzah, Hamiza (Faculty of Business and Management, 2014)
This paper is made to finding out about the factors that contributed to the determining the dividend policy among plantation companies listed in Bursa Malaysia. The secondary data for analysis is retrieved from UiTM Johor Datastream and the sample of this study comprises of 7 listed companies from the Bursa Malaysia main board on over 10 years period from year 2004 to 2013. Methodology used for this study is by using the Multiple Linear Regression with panel data. In our study, the dependent variable is dividend policy measured by dividend payout and the independent variables are profitability, liquidity, current earnings and growth opportunities. Based on the variables, the study aim is to explore the effects of profitability (ROE), liquidity (CR), current earnings (EBIT) and growth opportunities (Market Price to Book Value) towards the company dividend policy deicision. Thus, the result of this research paper will help the company especially the investors to take steps of strategies and decision making based on the dividend policy